P034 DISRUPTive liquid biopsies in Inflammatory Bowel Disease (DISRUPT-IBD): Release of exosomal and molecular tissue signals by transabdominal ultrasound?. (21st January 2022) - Tran, F; Scharmacher, A; Mishra, N; Barann, N; Sievers, L K; Juzenas, S; Bernardes, J P; Lessing, M; Lassen, A; Rosenstiel, P; Schreiber, S
Abstract: Background: A major drawback in diagnosis and monitoring of IBD are insufficient biomarkers that do not correlate well with tissue disease activity. Inflammation and cellular stress lead to an increased release of exosomes (Lipinski et al, 2019, EMBO J) carrying inflammatory signal proteins as cargo (Wozniak et al, 2020, J Cell Biol). Interestingly, colorectal cancer cells strongly release tumor markers after stimulation by sonography waves, probably through the disruptive energy of standard ultrasound (D'Souza et al, 2009, PNAS). We thus hypothesize that application of ultrasound waves on inflamed intestinal tissue in active IBD induces the release of tissue-specific exosomes that can be detected in the peripheral blood and used as novel biomarkers. Methods: 26 patients with different degrees of disease activity and various ongoing therapies with IBD were included in a pilot trial. Serum was taken before and 30 minutes after diagnostic transabdominal ultrasound. Serum exosomes were precipitated (using ExoQuick) and exosomal (exo-)miRNA were isolated for miRNA sequencing using SeraMir protocol. Exosomal proteins were isolated for quantification of inflammatory markers (as exosomal cargo). Results: We found a correlation between exo-miRNA concentration and disease severity, determined by clinical assessment scores and sonographic findings. Exo-miRNA sequencing revealed a select few miRNAs to be induced by sonography. However, the overall composition of annotated miRNA transcripts did not separate samples according to sampling timepoints. Among these "inducible" exo-miRNA, we found hsa-miR-942, which is involved in cell cycle and Wnt signaling in intestinal epithelial cells, to be significantly induced in higher grade intestinal inflammation. The exosomal protein concentrations did not correlate with disease severity at baseline, but were increased after sonography in severe intestinal inflammation. We did not find markers of the inflammasome apparatus as inducible exosomal cargos. Conclusion: Sonography-induced exosomal markers, e.g., exo-miRNAs, could become novel biomarkers for intestinal inflammation in IBD. Further exploration of the functional role of inducible biomarkers and continued investigation of exosomal miRNA and protein profiling will be performed.